2014
DOI: 10.1136/bcr-2013-202326
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical treatment of skeletal class III malocclusion

Abstract: SUMMARYThe incidence of skeletal class III malocclusion has a mean of 3% in the Caucasian population, 5% in AfricanAmerican adolescents and about 14% in the Asian population. In India, the incidence of class III malocclusion is reported to be 3.4%. A patient having class III malocclusion shows findings ranging from edge-to-edge bite to large reverse overjet, with extreme variations of underlying skeletal jaw bases and craniofacial form. This is a case report of a 20-year-old man having skeletal class III maloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…8, Issue 1 sceptical about undergoing orthognathic surgery and prefer a non-surgical alternative. [5] Therefore, for improving the occlusal and incisal relationship between the maxillary and mandibular jaw bases in mild to moderate skeletal discrepancies, orthodontic camouflage is an alternative therapy that can be considered. [6] Not all cases of class III malocclusion require surgery.…”
Section: Treatment Resultmentioning
confidence: 99%
See 1 more Smart Citation
“…8, Issue 1 sceptical about undergoing orthognathic surgery and prefer a non-surgical alternative. [5] Therefore, for improving the occlusal and incisal relationship between the maxillary and mandibular jaw bases in mild to moderate skeletal discrepancies, orthodontic camouflage is an alternative therapy that can be considered. [6] Not all cases of class III malocclusion require surgery.…”
Section: Treatment Resultmentioning
confidence: 99%
“…4 Growing patient with developing Class III malocclusion can be corrected easily with growth modification appliance, however, patients who have reached the end of their growth potential must be camouflaged by orthodontic tooth movement with fixed appliances or corrected surgically. [5] The severity of Class III malocclusion in adults will determine whether the patient is a candidate for orthognathic surgery or orthodontic treatment. [6]The camouflage approach for the correction of class III malocclusion often includeproclination A 21-year-old female presented to the department of orthodontics and dentofacial orthopedic, with the chief complaint of great dissatisfaction with her smile and irregularly placed upper and lower front teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Class III malocclusion is a rare phenomenon, occurring among less than 0.5% and, mainly, in Asian and African populations 27 . The incidence of class III malocclusion is reported to be 3% in the Caucasian population, 3.4%.in India 5% in African-American adolescents and about 14% in the Asian population 28 .…”
Section: Figure 1 Face Profile View and Occlusion Relationships Charmentioning
confidence: 99%
“…The European studies had an average prevalence rate of 4.88%, and Indian populations had the lowest prevalence rate of 1.19 %. In the bygone days, Class III malocclusions were believed to be solely due to the prognathic mandible [7]. Present knowledge of etiology has revealed that it can occur due to maxillary retrognathism, mandibular prognathism, or a combination of both.…”
Section: Materiale şI Metodementioning
confidence: 99%
“…Ţările din Sud-estul Asiei au aratat o maximă a prevalenţei 15,80%, Europa 4,88%, iar India, cel mai mic nivel 1,19%. În trecut, se credea ca ele apar doar pe contul unui prognatism mandibular [7]. Actualmente, pentru pacienţii cu anomalii dento-maxilare clasa III-a, se descriu mai multe situaţii clinice: retrognatism maxilar (pseudoprognatism mandibular), prognatism maxilar propriu-zis, prognatism mandibular combinat cu retrognatism maxilar [2].…”
unclassified